Balancing Life, Shaping Minds: How Work-Life Balance, Workplace Environment, and Personality Drive Employee Productivity through Job Satisfaction - Helena Devinta Hardianti; Ignatius Ario Sumbogo (Universitas Pelita Harapan, 2025)
This study examines the influence of work–life balance, workplace environment, and the Big Five personality traits on employee productivity, with job satisfaction serving as a mediating variable. Using a quantitative research design and survey method, data were collected from 50 employees of PT X through structured questionnaires and analyzed using multiple linear regression. The findings reveal that the workplace environment does not significantly affect employee productivity, either directly or indirectly. Work–life balance exerts a significant influence on productivity, both directly and indirectly, while the Big Five personality traits significantly affect productivity only indirectly. Job satisfaction, however, does not significantly mediate these relationships. Overall, the study concludes that work–life balance plays a crucial role in shaping employee satisfaction and productivity, while the workplace environment does not exert a meaningful influence. The Big Five personality traits predict productivity but not job satisfaction, and job satisfaction itself does not significantly determine productivity within the company.